Race, Class and the Stigma of Place: Moving to “Opportunity” in eastern Iowa - Keene, Danya E (2010)
In this paper, we explore how the stigmatization of place is transported to new destinations and negotiated by those who carry it. Additionally, we discuss the implications of ‘spatial stigmatization’ for the health and well-being of those who relocate from discursively condemned places such as high-poverty urban neighborhoods. Specifically, we analyze in-depth interviews conducted with 25 low-income African American men and women who have moved from urban neighborhoods in Chicago to predominantly white small town communities in eastern Iowa. These men and women, who moved to Iowa in the context of gentrification and public housing demolition, describe encountering pervasive stigmatization that is associated not only with race and class, but also with defamed notions of Chicago neighborhoods.